A Hopeful Sea-Monster: A Very Large Homologous Recombination Event Impacting the Core Genome of the Marine Pathogen Vibrio anguillarum - Coyle, Nicola M.; Bartie, Kerry L.; Bayliss, Sion C.; Bekaert, Michaël; Adams, Alexandra; McMillan, Stuart; Verner-Jeffreys, David W.; Desbois, Andrew P.; Feil, Edward J. (Frontiers in Microbiology, 2020)
Vibrio anguillarum is the causative agent of vibriosis in many species important to aquaculture. We generated whole genome sequence (WGS) data on a diverse collection of 64 V. anguillarum strains, which we supplemented with 41 publicly available genomes to produce a combined dataset of 105 strains. These WGS data resolved six major lineages (L1-L6), and the additional use of MLSA clarified the association of L1 with serotype O1 and Salmonidae hosts (salmon/trout), and L2 with serotypes O2a/O2b/O2c and Gadidae hosts (cod). Our analysis also revealed a large-scale homologous replacement of 526-kb of core genome in an L2 strain from a con-specific donor. Although the strains affected by this recombination event are exclusively associated with Gadidae, we find no clear genetic evidence that it has played a causal role in host specialism. Whilst it is established that Vibrio species freely recombine, to our knowledge this is the first report of a contiguous recombinational replacement of this magnitude in any Vibrio genome. We also note a smaller accessory region of high single nucleotide polymorphism (SNP) density and gene content variation that contains lipopolysaccharide biosynthesis genes which may play a role in determining serotype.